Allogeneic Mesenchymal Precursor Cells Promote Healing in Postero-lateral Annular Lesions and Improve Indices of Lumbar Intervertebral Disc Degeneration in an Ovine Model. Issue 17 (September 2016) - Freeman, Brian J.C.; Kuliwaba, Julia S.; Jones, Claire F.; Shu, Cindy C.; Colloca, Christopher J.; Zarrinkalam, Mohammad R.; Mulaibrahimovic, Adnan; Gronthos, Stan; Zannettino, Andrew C. W.; Howell, Stuart
Abstract : Study Design: In-vivo ovine model of intervertebral disc degeneration (IVD) to evaluate treatment with stem cells. Objective: To determine if stem cells delivered to the nucleus pulposus (NP) or the annulus fibrosus (AF) of degenerated lumbar IVDs leads to improved indices of disc health. Summary of Background Data: Previous studies assessing the efficacy of stem cell injections into degenerated IVDs have reported positive findings. However, studies have been limited to small animals, targeting solely the NP, with short term follow-up. Methods: Mesenchymal precursor cells (MSC) were obtained from the iliac crest of 8-week-old sheep. IVD degeneration was induced by postero-lateral annulotomy at three lumbar levels in eight 2-year-old sheep. Six months later, each degenerated IVD was randomized to one of three treatments: Injection of MSC into (i) previously incised AF (AFI), (ii) NP (NPI), or (iii) no injection (negative control, NC). The adjacent IVD received injection of phosphate buffered saline into NP (positive control, PC). Radiographs and magnetic resonance imaging scans were obtained at baseline, 6, 9, and 12 months. Discs were harvested at 12 months for biochemical and histological analyses. Results: IVD degeneration was consistently observed postannulotomy, and characterized by reduced disc height index (DHI), disc height (DH), glycosaminoglycan (GAG) content, and increased grade of disc degeneration. Six months after stem cell injection, DHI and DH had recovered in AFI and NPI groups when compared with NC group ( P  < 0.01). Mean Pfirrmann grade improved from 3.25 to 2.67 (AFI group) and from 2.96 to 2.43 (NPI group). Mean histopathological grade improved for both AFI ( P  < 0.002) and NPI ( P  < 0.02) groups. Both AFI and NPI groups demonstrated spontaneous repair of the postero-lateral annular lesion. Conclusion: In this large animal model, injection of MSCs into the annulus fibrosus or the nucleus pulposus of degenerated IVD resulted in significant improvements in disc health. Level of Evidence: N/A Abstract : Supplemental Digital Content is available in the text